The challenges of doing criminology in the big data era: towards a digital and data-driven approach - Smith, Gavin J. D. (The British journal of criminology, 2017)
This paper considers emerging challenges and opportunities confronting criminology in the age of Big Data. The mass proliferation of digital media/recording devices into social life is transforming in profound ways how crime is organized, perpetrated, experienced, represented, detected and controlled. Moreover, the extensive daily use of these technologies by institutions and individuals alike produces immense quantities of data that mediate social events, actions and experiences in significant, if subtle, ways. Such data are means of communication, knowledge and entertainment, as well as resources for analytic and criminal manipulation and community mobilization. We suggest that criminology must develop a digital specialism which investigates the multifaceted role performed by digital technologies as intersectional and transformative mediums in the crime and justice field.